HUMAN INTERACTION IN URBAN SPACES: A QUANTITATIVE ANALYSIS IN URBAN PARK, SHAH ALAM CITY, SELANGOR - Ibrahim, Filzani Illia; Omar, Dasimah; Nik Mohamad, Nik Hanita (PLANNING MALAYSIA, 2017)
This paper aims to provide valuable insight of the various dimensions of human needs’ towards open spaces. This study employed a mixed method research design involving both quantitative and qualitative methods that were utilised to identify and evaluate the human-human interaction and human-nature interaction in the area of study. Primary data was gathered by using questionnaire survey that was administered to 861 respondents who were visitors to public parks. The finding of this study is intended to show the main domains that reflect human needs’ toward open spaces together with perceived benefits to the open space users.